Organocatalytic 1, 3‐Dipolar Cycloaddition Reaction of β‐Keto Amides with Azides – Direct Access to 1, 4, 5‐Trisubstituted 1, 2, 3‐Triazole‐4‐carboxamides. Issue 10 (21st March 2016) - Zhou, Xiao; Xu, Xianhong; Liu, Kun; Gao, Hua; Wang, Wei; Li, Wenjun
Abstract: Organocatalytic [3+2] 1, 3‐dipolar cycloaddition reactions of β‐keto amides with azides catalyzed by 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) have been developed. This strategy generates 1, 4, 5‐trisubstituted 1, 2, 3‐triazole‐4‐carboxamides in high yields and regioselectivities at room temperature. The reaction conditions have been optimized, and the scope of the β‐keto amide and azide have been investigated. A mechanism for the reaction is also proposed. Abstract : The [3+2] organocatalytic 1, 3‐dipolar cycloaddition reactions of β‐keto amides with azides are catalyzed by 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU). This strategy generates 1, 4, 5‐trisubstituted 1, 2, 3‐triazole‐4‐carboxamides in high yields and regioselectivities at room temperature.